Economic comparison of SDI and center pivots for various field sizes - O'Brien, Daniel, author; Rogers, Danny H., author; Lamm, Freddie, author; Clark, Gary, author (Colorado State University. Libraries, 1998)
Subsurface drip irrigation (SDI) systems are feasible for some field crops and field arrangements using current levels of technology. Sprinkler irrigation systems have an economic advantage over SDI systems for the typical case where full-size center pivots can be used. However, center pivots lose important economies of scale as fixed investment costs are concentrated onto smaller acreages. Thus, the cost advantage for a center pivot system diminishes as field size is reduced. This analysis assumes an existing flood-irrigated field with an existing well or water supply that is centrally located at the edge of the field. This flood-irrigation system is to be converted to either a center pivot or SDI system. The well is fully depreciated, but not in need of replacement. Investment cost estimates for alternative irrigation systems and estimated crop budgets for irrigated com and summer fallow wheat in western Kansas are used to project annual profitability for the alternative irrigation and cropping systems. The objective is to compare center pivot and SDI system costs and net returns per acre for several field sizes.
Not digitized by CSUL Digital Services.
Presented at the Central Plains irrigation short course and exposition on February 17-18, 1998 at the Camino Inn in North Platte, Nebraska.